Marketing Mix Strategy to Increase the Number of Wedding Events in Geo Open Space - Yanti, Ni Kadek Dwi Darma; Widaharthana, I Putu Esa; Swandewi, Ni Kadek (PT FORMOSA CENDEKIA GLOBAL, 2024)
The demand for unique and memorable wedding venues is increasingly in demand, providing event spaces that suit the wedding theme and the couple's needs. One of the wedding venue providers in the Badung area, specifically in Kerobokan Village is Geo Open Space. This research intend to understand the marketing mix strategy for wedding events at Geo Open Space.The method used in this research is descriptive qualitative with data collection conducted through interviews, documentation and observation. The analysis technique uses the 7P marketing mix and the SWOT matrix. Based on the 7P marketing mix, the conclusion is that Geo Open Space can add products according to client needs, such as indoor venues, create attractive wedding packages by adjusting the existing target market, Geo Open Space can maximize the use of social media and product promotion and improve parking area facilities. Furthermore, Geo Open Space can collaborate with wedding organizers and decoration vendors potential.